2021
DOI: 10.1111/joim.13349
|View full text |Cite
|
Sign up to set email alerts
|

The roles of free iron, heme, haemoglobin, and the scavenger proteins haemopexin and alpha‐1‐microglobulin in preeclampsia and fetal growth restriction

Abstract: Background Preeclampsia (PE) is a complex pregnancy syndrome characterised by maternal hypertension and organ damage after 20 weeks of gestation and is associated with an increased risk of cardiovascular disease later in life. Extracellular haemoglobin (Hb) and its metabolites heme and iron are highly toxic molecules and several defence mechanisms have evolved to protect the tissue. Objectives We will discuss the roles of free iron, heme, Hb, and the scavenger proteins haemopexin and alpha‐1‐microglobulin in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 179 publications
0
12
0
1
Order By: Relevance
“…Since free-form sub Fe ions (Fe 2+ ) can cause the production of FR or reactive oxygen species (ROS), which can lead to peroxidation and FR chain reactions and nally to molecular damage [11]. A high Fe content will increase the risk of HDCP (e.g., PE) [10,13]. The results of this study showed that there was a signi cant difference in Fe content in maternal blood, placenta and umbilical cord blood in the normal group (Figure . 2.…”
Section: Discussionmentioning
confidence: 99%
“…Since free-form sub Fe ions (Fe 2+ ) can cause the production of FR or reactive oxygen species (ROS), which can lead to peroxidation and FR chain reactions and nally to molecular damage [11]. A high Fe content will increase the risk of HDCP (e.g., PE) [10,13]. The results of this study showed that there was a signi cant difference in Fe content in maternal blood, placenta and umbilical cord blood in the normal group (Figure . 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that, in 18% of PE patients, the transferrin saturation levels are high, which is related to iron overload [ 114 ]. During normal pregnancy, the maternal plasma blood volume increases at the first trimester and can increase by 30–50% at the third trimester [ 115 ]. This hypervolemia has little effect on pregnancy complications, while increased plasma volume can cause changes in iron concentration and other factors, which have different effects on normal pregnancy and PE pregnancy [ 116 ].…”
Section: Ferroptosis and Pre-eclampsiamentioning
confidence: 99%
“…Failure to transform the branches of the placental spiral artery restricts the flow of maternal blood to the villus space, and continuous ischemic and perfusion damages the developing placental villi. Compared with normal pregnancy, the volume and surface area of the fetal FGR placenta decreases significantly, placental thickness increases, the blood vessels in the villi decrease or disappear, the lumen narrows or even becomes occluded, and the percentage of villi, capillaries, and surface area of the villi are all reduced ( Erlandsson et al, 2021 ). Through experiments in guinea pigs, Canas et al found that FGR is associated with a heterogeneous pro-constrictive vascular remodeling that sets in during pathologic pregnancy to sustain fetal blood redistribution ( Cañas et al, 2017 ).…”
Section: Pathophysiology and Clinical Characteristics Of Pe And Fetal...mentioning
confidence: 99%